Участь неурядових організацій в реалізації міжнародно-правових норм у галузі охорони навколишнього середовища - Медведєва, М. О.; Медведева, М. О.; Medvedeva, М. (My University, 2012)
The issue analyzes the peculiarities and forms of the participation of international and national non-governmental organizations in the implementation of international environmental legal rules and principles. The author concludes that notwithstanding the absence of recognition of their international legal personality non-governmental organizations participate in international environmental legal relations, and also encourage the implementation of international environmental law by means of direct usage of rights envisaged in multilateral environmental agreements, compliance with obligations and prohibitions and enforcement of environmental rules in international courts.
Медведєва М. О. Участь неурядових організацій в реалізації міжнародно-правових норм у галузі охорони навколишнього середовища / М. О. Медведєва // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 84-94.
Keywords: міжнародне право навколишнього середовища; форми участі міжнародних неурядових організацій в реалізації права навколишнього середовища; норми і принципи міжнародного права навколишнього середовища; природоохоронні норми; международное право окружающей среды; формы участия международных неправительственных организаций в реализации права окружающей среды; нормы и принципы международного права окружающей среды; природоохранные нормы; international environmental law; forms of participation of international non-governmental organizations in the implementation of environmental law; norms and principles of international environmental law; environmental regulations